MAHASISWA JURUSAN PENDIDIKAN KEOLAHRAGAAN UNIVERSITAS NEGERI GORONTALO - Datau, Supriyadi (JURNAL HEALTH AND SPORT, 2011)
the result of research was the instructional material product ofvolley ball II subject matter.According to the experts that the product ofinstructional material is upper of three (3) point or involved in good/correct/clear category. Based on experiment in large scale total score frequency of students response to the instructional material of volley ball II subject,argues that there are 98,96% of 192 score total students involved in good category, I ,04Yo of 192 score total students involved in average category,and no one ofthe students involved in lack category.